Deforestation decreases spatial turnover and alters the network interactions in soil bacterial communities. (August 2018) - Tian, Jing; He, Nianpeng; Kong, Weidong; Deng, Ye; Feng, Kai; Green, Sophie M.; Wang, Xiaobo; Zhou, Jizhong; Kuzyakov, Yakov; Yu, Guirui
Abstract: Despite important progress in understanding the influence of deforestation on the bacterial α diversity and community structure at local scales, little is known about deforestation impacts in terms of spatial turnover and soil bacterial community network interactions, especially at regional or global scales. To address this research gap, we examined the bacterial spatial turnover rate and the species networks in paired primary and secondary forest soils along a 3700-km north-south transect in eastern China using high-throughput 16S rRNA gene sequencing. The spatial turnover rate of bacterial communities was higher in primary forests than in secondary, suggesting deforestation increased biotic homogenization at a large geographic scale. Multiple regression on matrices analysis revealed that both geographic distance and soil properties (especially soil pH and organic matter availability) strongly affected bacterial spatial turnover. Through the phylogenetic molecular ecological network approach, we demonstrate that the bacterial network of primary forests was more intricate than in secondary forests. This suggests that microbial species have greater niche-sharing and more interactions in primary forests as compared to secondary forests. On the other hand, the bacterial network in secondary forests was more modular, and the taxa tended to co-occur, with positive correlations accounting for 82% of all potential interactions. In conclusion, our findings demonstrate that anthropogenic deforestation has clear effects on bacterial spatial turnover and network interactions, with potential for serious consequences such as microbial diversity loss in primary forests. Highlights: Deforestation decreased bacterial spatial turnover rate at large geographic scale. Soil pH and SOM availability strongly affected bacterial spatial turnover rate. Bacterial networks were more intricate in primary than in secondary forests. Bacterial taxa tended to co-occur in secondary forest network. The major connectors in the secondary forest network were Proteobacteria.